The flood rains come - Thomas Hart Benton:::Creator::::::::::::
The flood rains come, from The Grapes of Wrath, vol.2 p.531, illustrated edition, by Thomas Hart Benton, a native of eastern Oklahoma, who was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate. "For two days the earth drank the rain until the earth was full... At last the mountains were full, and the hillsides spilled into the streams...and sent them roaring down the canyons into the valleys."